VALUE OF SECONDARY INFLAMMATORY SIGNS ON ULTRASOUND IN EVALUATION OF ACUTE APPENDICITIS - Amin, Zafar; Qayyum, Adil; Mumtaz, Syed Naveed; Noor, Asma; Adil, Ruqqayia (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the sensitivity, specificity, positive and negative predictive values using secondary Ultrasound features of inflammation, in suspected patients of acute appendicitisStudy Design: Cross sectional validation study.Place and Duration of Study: Radiology department, Combined Military Hospital Bahawalpur, from Apr 2016 to Mar 2017.Methodology: A total of 178 suspected patients of acute appendicitis having right lower quadrant pain were referred for ultrasound. Patient’s ages ranges from 5-55 years. Primary and secondary signs of inflammation of acute appendicitis were assessed on ultrasound. Patient having positive primary sign alone or at least two or more secondary signs were labeled as acute appendicitis and underwent surgery. Statistical data was analyzed using Medcalc 17.5.5.Results: When only Secondary sonographic signs of inflammation were considered in suspected cases of acute appendicitis, then Sensitivity was 88.2%, specificity 72.5%, positive predictive value 81.1%, accuracy 81.5% and negative predictive value was 82.2%. Sensitivity and accuracy were increased to 93.7% and 87.6% % respectively, when primary and secondary signs were considered collectively.Conclusion: Ultrasound examination should be the first imaging modality to be carried out in suspected cases of acute Appendicitis with particular emphasis on secondary ultrasound features, as primary features are not always present. Presence of both these signs confidently diagnose Acute Appendicitis.